Sosialisai Tentang Pentingnya Penanaman Tanaman Obat Untuk Mewujudkan Masyarakat Sehat Di Kecamatan Medan Helvetia, Kota Medan - Dhea Nur Fadhilah; Suharyanisa Suharyanisa; Jon Kenedy Marpaung; Juli Susanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Medicinal plants are plants with positive pharmacological effects on the human body and are usually grown on a home or communal scale. These medicinal plants can then be used as traditional medicine which can be made easily. The plants chosen are usually plants that can be used to treat simple health problems such as flu and coughs. Medicinal plants can increase the body's immunity because they can prevent disease through the secondary metabolites they contain. In this service activity, two activities were carried out separately, namely socialization and planting medicinal plants with residents. The outreach was carried out to provide information to the residents of Medan Helvetia District regarding medicinal plants so that these medicinal plants can be useful after being planted. Planting is also carried out to increase awareness regarding land use, as well as being a starting point for residents in cultivating medicinal plants. This socialization on the use of family medicinal plants aims to provide information to the people of Kexamatan Medan Helvetia in using medicinal plants. It is hoped that this community service activity will help increase public knowledge about the importance of planting and utilizing medicinal plants to create a healthy society.